Near-edge X-ray absorption spectroscopy signature of image potential states in multilayer epitaxial graphene. - Coelho Neto, Paula Maciel (2016)
Single layer behavior in multilayer epitaxial graphene has been a matter of intense investigation. This is due to the layer decoupling that occurs during growth of graphene on some types of substrates, such as carbonterminated silicon carbide. We show here that near-edge X-ray absorption spectroscopy can be used to observe the signature of this decoupling. To this end, samples of multilayer graphene from silicon carbide sublimation were grownwith different degrees of decoupling. Raman spectroscopy was used to infer the degree of structural decoupling. X-ray grazing-incidence diffraction and scanning tunneling microscopy showed that growth initiates with the presence of bilayer graphene commensurate structures, while layer decoupling is associated to the formation of incommensurate structures observed for longer sublimation time. Near-edge X-ray absorption spectroscopywas used to probe the electronic states above the Fermi energy. Besides the σ* and π* empty states, image potential states are observed and show a clear change of intensity as a function of incident angle. These image potential states evolve from a graphite- to graphene-like behavior as a function of growth time and can be used to infer the degree of structural coupling among layers.